Effect of gallic acid on ram semen spermatological parameters at +4 ⁰c storage - Şükrü Güngör; Muhammed Enes İnanç; Ayhan Ata (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this study was to investigate the effect of different rate of gallic acid on ram semen liquid storage in non-breeding season. Materials and Methods: In this study, four Merino rams (2-3 ages) were used and belonging to the special sheep farm in Callica, Burdur/ Turkey. Ejaculates were collected from the rams using a electroejaculator, the ejaculates containing spermatozoa with >80% motility and concentrations higher than 1.5x10⁹ spermatozoa/ml were mixed and used in the study. The mixed ejaculates were divided into four equal aliquots and samples were extended with tris containing 0 mM (control), 2 mM, 5 mM, 10 mM gallic acid and they were stored at 4°C. After the groups were created, sperm motility (%), morphologic integrity (%), membrane integrity subjective (Hipo Osmotic Swelling Test, HOS test, %) were examined 24 hour intervals until 96 hour. Results: The highest motility at 48. hour was seen gallic acid 2 mM (72.7±5.3%) and 5 mM (69.4±4.8%) groups compared the control (51.0±2.7%) group (P<0.05). At the end of the storage time to (96. hour) gallic acid 2mM and gallic acid 5 mM was protected to sperm motilities compared the control group (P<0.05). Also, gallic acid 10 mM were decreased to the membrane integrity compared to the control group (P < 0.001). There were no significant differences among groups on abnormal spermatozoa rate in every storage period (P > 0.05) but, there was a statistically significant increase in abnormal spermatozoa rate at the depending on storage time (P < 0.001). Conclusion: In conclusion, gallic acid 2 mM and gallic acid 5 mM should be supplement to ram semen extender at short term storage period on non-breeding season for improvement of sperm motility.